Model Place-Based Education Dalam Pembelajaran SKI Untuk Menumbuhkan Karakter Ta’addub dan Peduli Budaya Lokal di Madrasah Ibtidaiyah - Agus Salim Chamidi (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2026)
This study aims to analyze the implementation of the Place-Based Education (PBE) model in teaching Islamic Cultural History (Sejarah Kebudayaan Islam, SKI) to foster ta'addub (civilized character) and local cultural awareness among sixth-grade students of Madrasah Ibtidaiyah (MI). In the digitalization era, primary school-aged youths tend to experience cultural erosion due to global popular culture exposure and gadget addiction, necessitating a pedagogical reconstruction of history education rooted in the students' immediate environment. The research method employed is library research, with data collection techniques utilizing critical reviews of curriculum documents, teaching modules, scientific journals, and literature relevant to the PBE model and the proselytization (dakwah) history of Walisongo. The results indicate that the implementation of the PBE model, adapted through four phases (local exploration, curriculum connection, community contribution, and place reflection), effectively bridges the cultural dakwah materials of Walisongo with the students' daily realities. This model successfully nurtures ta'addub by internalizing the exemplary values of the saints (wali), who were adaptive and respectful toward local traditions. Furthermore, place-based activities within PBE, such as creating cultural bulletin boards, effectively stimulate MI students' awareness to safeguard and preserve local Islamic artistic heritage against the threats of digitalization. This study concludes that place-based SKI learning serves as a contextual and meaningful pedagogical strategy to reinforce the moral and cultural identity of children within Islamic primary education